NEW TRANS-1,2- CYCLOHEXYLDIAMINO-NN,N’N’ (CH2CO2)(CH2CO2H)3 ANION CONTAINING ADDUCTS AND DERIVATIVES: SYNTHESIS AND INFRARED STUDY - GORGUI AWA SECK; ABOUBACRY SENE; LIBASSE DIOP (Journal of Engineering Studies and Research, 2017)
Five Cyclohexyldiamino-NN, N’N’(CH2CO2)(CH2CO2H)3 anion containing adducts and derivatives with tin, antimony and mercury halides have been synthesized and characterized by infrared spectroscopy. The suggested structures are discrete, the anion behaving as a monodentate or a monochelating ligand: the environments around the metallic centres are trigonal bipyramidal or octahedral.The carboxylic groups and the cation, when involved in extra OH---O, OH----Cl or NH---Cl or O hydrogen bonds may lead to supramolecular architectures.